Wavelet Analysis and Contrast Modification in the Study of Cell Structures Images - Lyashenko, V.; Kobylin, O.; Selevko, O. (WARSE, 2020)
Image processing is one of the data analysis tools. It is also a tool for getting more information. Such a tool occupies a special place for data research in the field of medicine. The imaging of cellular structures is an important example of medical data. The article describes the procedure for analyzing images of cellular structures. This procedure includes: changing the contrast of the image and using wavelet analysis to highlight the edges of objects in the image. Examples are given. The efficiency of the considered procedure is shown in comparison with classical methods.
Keywords: Wavelet Analysis; Image Processing